Value aggregation of pine (Araucaria angustifolia) nuts agro-industrial waste by cellulose extraction (Research, Society and Development, 2021)
Araucaria (Araucaria angustifolia) is a tree species found in the Southeast and South of Brazil. It is also known as Brazilian pine, presenting fruits of high acceptance. However, its processing generates by-products that are little used. Thus, this work aimed to extract and characterize the cellulose obtained from the pinion husk, as well as to evaluate the contents of ash, lignin, cellulose and α-cellulose in its composition. The raw material and the extracted cellulose were characterized by X-ray fluorescence analysis (XRF), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). As for the contents of chemical composition detected, the husks showed 1.6% ash, 7% extractives, 34% lignin and 55% cellulose, being 46% α-cellulose and 9% hemicellulose. It was observed by XRD that the removal of amorphous materials resulted in a gain of crystallinity (from 19 to 33%). Proving the efficiency of the extraction, the characterization of the cellulose obtained was shown to be of high purity, since the main band of the lignin (FTIR) and the amorphous materials of the cellulosic sample (TGA) disappeared. Finally, this work shows that the pinion bark is a rich source of cellulose, making it possible to obtain nanocrystals.